Handbook of research on innovations and applications of AI, IoT, and cognitive technologies - Zhao, Jingyuan 1968-; Kumar, V. Vinoth (IGI Global, Publisher of Timely Knowledge, 2021)
"This book provides perspectives of academics and industrial practitioners offering the latest innovations and applications of artificial intelligence (AI), Internet-of-Things (IoT) and cognitive based smart systems to provide information for all those interested in AI, IoT and Cognitive Technologies in emerging and developed economies in terms of their respective development situation toward public policies, technologies and intellectual capital, innovation systems, competition and strategies, marketing and growth capability, governance and relegation model etc" - Provided by publisher
Includes bibliographical references and index
Keywords: Internet of things / Industrial applications; Artificial intelligence / Industrial applications